Xenophobia and Islamophobia in Europe - Taras, Ray, 1946- (Edinburgh University Press, 2012)
Are anti-Muslim attitudes becoming the spectre that is haunting Europe? Is Islamophobia as widespread and virulent as is made out? Or do some EU societies appear more prejudiced than others? To what extent are European fears about unmanaged immigration the basis for scapegoating Muslim communities? And is there an anti-elitest dimension to Europeans' protest about rapid demographic change occurring in their countries?This cross-national analysis of Islamophobia looks at these questions in an innovative, even-handed way, steering clear of politically-correct clichés and stereotypes. It cautions.